2005
DOI: 10.1111/j.1749-4486.2005.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Is ultrasound useful for evaluating paediatric inflammatory neck masses?

Abstract: Ultrasound is a useful modality in the evaluation of acute cervical masses but is observer dependent and has a relatively low sensitivity in detecting whether or not pus is present. The clinical indicators for the presence of an abscess are discussed and clinicians should combine clinical findings with the ultrasound findings in order to determine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 5 publications
2
17
0
1
Order By: Relevance
“…However, other authors demonstrated relatively low accuracy of ultrasound, with sensitivity ranging from 60 to 70% and specificity of 33 to 88% [5,6]. Most authors attribute this limited accuracy to the inability of paediatric patients to actively cooperate during imaging studies [5,6]. In their response to Douglas et al [5], Ho et al [8] stated the advantage of repeated ultrasound, and claimed much greater accuracy when ultrasound studies are performed by experienced staff [8].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, other authors demonstrated relatively low accuracy of ultrasound, with sensitivity ranging from 60 to 70% and specificity of 33 to 88% [5,6]. Most authors attribute this limited accuracy to the inability of paediatric patients to actively cooperate during imaging studies [5,6]. In their response to Douglas et al [5], Ho et al [8] stated the advantage of repeated ultrasound, and claimed much greater accuracy when ultrasound studies are performed by experienced staff [8].…”
Section: Discussionmentioning
confidence: 94%
“…In their prospective study of 23 patients, Quraishi et al [7] demonstrated up to 100% surgically proven accuracy of ultrasound for the evaluation of neck abscesses in children. However, other authors demonstrated relatively low accuracy of ultrasound, with sensitivity ranging from 60 to 70% and specificity of 33 to 88% [5,6]. Most authors attribute this limited accuracy to the inability of paediatric patients to actively cooperate during imaging studies [5,6].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…They evaluated lesions of probable inflammatory nature and found a sensitivity of 96 %, that is, the fraction of the patients who showed a positive response in the ultrasonographic examination among those individuals who had the disease [8][9][10][11][12]. On the contrary, Douglas et al [13] found a 65 % sensitivity for the examination. Along this same line of research, Pallagatti et al [14] and Nisha et al [12] respectively determined an accuracy of 88.9 and 97.1 % for US.…”
Section: Discussionmentioning
confidence: 99%